Cat dog - Fox, Mem 1946- (Puffin Books / Penguin Random House Australia, 2021)
"Join an unlikely animal trio for some irresistibly funny antics in this read-aloud gem from bestselling, award-winning and much-loved author Mem Fox and acclaimed illustrator Mark Teague. There is a cat in this book. There is also a dog. And there is a whole lot of crazy stuff going on ... Right?"--Provided by publisher